Knowledge and Attitudes of the Inhabitants of a Rural Canton about the Prevention of Colorectal Cancer - Carlos David Castañeda Guillot; Blanca Cristina Estrella López; Diego Fernando Vaca Sánchez (Revista Finlay, 2023)
Foundation: colorectal cancer is one of the main causes of death from cancer in Ecuador, both in men and women. Objective: to evaluate the knowledge and attitudes of residents in a rural canton in relation to the prevention of colorectal cancer. Method: a qualitative-quantitative, descriptive and correlational study was carried out. The study was carried out between October and December 2022 and 245 residents of a rural canton participated. The technique for data collection was the survey. The questionnaire was designed for this purpose with 22 closed questions. The survey was anonymous. All respondents gave informed consent to participate in the study and were informed of its purpose. The results obtained were processed with Microsoft Excel 2016 and statistically analyzed using SPSS 25 software. Non-parametric tests were performed for statistical significance between variables. Results were presented in amounts and percentages with rounding adjustments. Results: a large proportion of respondents were aware that early diagnosis of colorectal cancer increases the chances of cure, however, half of respondents knew that this type of cancer can develop without presenting symptoms. Knowledge about risk factors and symptoms of colorectal cancer in the study group was low. In general, the level of knowledge of the respondents about colorectal cancer and its prevention was mostly sufficient. Conclusions: the results indicate that the level of knowledge and attitudes of the residents of the rural canton in relation to colorectal cancer and its prevention is not yet satisfactory. The need to implement intensive educational activities is highlighted, mainly focused on promoting colorectal cancer screening.